Trajetos no labirinto: história de vida dos portadores de doenças oncológicas em uso de transfusões sanguíneas na cidade de Natal/RN - Costa, João Evangelista da (2013)
The studies paths in the maze: life story of individuals with oncological diseases into use of blood transfusion in Natal has the hemotherapy as a primordial procedure to review the relationship between users of oncological health and the due ramifications. The hemotherapy looks for supply the organic needs through blood transfusion, which acquires vital function to the ones that have cancer, because it might reestablish the functionality of the organism throughout the raising of blood components. The impact over the transfusion affects emotionally and physically the users life. Aiming to reflect on these impacts, this study tried, through narratives of lives, rescue their experience since their knowledge of the disease until the time of blood transfusion using. It s about an exploratory-descriptive study, where the qualitative approach uses the theoretical-methodological reference of the oral life history to analyze a colony consisting of five users of health diagnosed with cancer, with achievement of at least three blood transfusions, the clinic Núcleo de Hematologia e Hemoterapia - UFRN, in Natal-RN. The network, in turn, was composed by employees of both sexes, regardless of age, who voluntarily agreed to participate in the study. The data collection, with approval of the Ethics Committee in Research, Liga Norte Riograndense Contra o Cancer, on the number 001/001/2012, occurred through semi-structured interviews, recorded individually in the home context that was previously chosen by employees. The methodological procedure occurred with the transcription of the interviews and their transcreations, and analysis of reports by thematic content analysis. At the reading orientation and interpretation of the employees stories, were discussed three categories of analysis: the impact on psychological REVIEW; impact on socialization and group membership, the environment and the impact of blood transfusion on treatment. Based on the narrative of the life histories of employees, we conclude that the experiences and feelings, hope and sorrow, pain and faith, even when facing a disease like cancer, bring lots of teaching and learning to health professional that deposits humanization health and reinstate hemotherapy forms of clinical critical